Transtextuality in an Animated Film by Koji Yamamura - Vidaurre-Arenas, Carmen Vitaliana (2022)
We analyzed the short-animated film by Kōji Yamamura Franz Kafka's A Country Doctor (Kafuka: Inaka Isha, 2007) using some of G. Genette's conceptual proposals. The analysis allows us to observe how the nonsense, ironies, identifications, contrasts, and other literary elements like hypotext are emphasized and intensified in the hypertextual film version. The film shows a lucid look at the workings of Kafka's tale and an imagination expressed through poetic and other elements of animated film. The film introduces those elements into the new graphic and audiovisual version of the story. The work achieves syncretism from affinities between the adapted work and some characteristics of Kyōgen performing art introduced in this film.